2013
DOI: 10.4103/1119-3077.110124
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of presentations at a free eye clinic in an urban state hospital

Abstract: Preventable causes of blindness were quite common among the patients. There is a need for community education to reduce the prevalence of these diseases in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
2
8
2
Order By: Relevance
“…This corroborates the report of Fotouhi [7] who in a study on eye care utilization in Tehran population in 2006 reported that more women sought eye care than men. Hassan et al also corroborated the same thing in a similar environment in the same region although a hospitalbased study, [8] while Clendenin [9] in 1997 reported that no significant difference between genders was found in terms of eye services utilization. [9] The age group below 45 years was more than the others probably because they are more active.…”
Section: Discussionsupporting
confidence: 53%
“…This corroborates the report of Fotouhi [7] who in a study on eye care utilization in Tehran population in 2006 reported that more women sought eye care than men. Hassan et al also corroborated the same thing in a similar environment in the same region although a hospitalbased study, [8] while Clendenin [9] in 1997 reported that no significant difference between genders was found in terms of eye services utilization. [9] The age group below 45 years was more than the others probably because they are more active.…”
Section: Discussionsupporting
confidence: 53%
“…The five least common cases were pan-uveitis, HZO, pingueculum, painful blind eye and orbital cellulitis. This is in contrast with some studies in Nigeria with higher numbers probably because they were free outreach programmes with large turn outs [3,4,5].…”
Section: Discussioncontrasting
confidence: 71%
“…[1] Adenuga et al in a study at the Nigerian Airforce Hospital Jos, Northern Nigeria reported the commonest eye disorders as allergic conjunctivitis (42%), refractive error and presbyopia (33%) and degenerative conjunctival diseases (5%), cataract (3.75%), and glaucoma (2.65%). [2] Similarly, a study by Hassan et al in South-West Nigeria noted that vernal conjunctivitis (21.1%) was the commonest disorder seen; this was followed by cataract (14%), glaucoma (11.1%), and refractive error (20.7%) [3]. In an outreach in North-west Nigeria, Monsudi et al reported the predominant ocular diseases to be cataract (32.3%), glaucoma (18.3%), and refractive error (17.9%) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable study by Waziri-Erameh and Omoti [34][35][36][37][38][39] reported similar findings with majority of patients (70.18%) with visual acuity better than 6/18, 25.49% with visual acuity between 6/60-6/18 while 4.33% had visual acuity worse than 6/60. However, one study by Hassan et al [40][41][42][43][44][45] reported higher percentage of patients with visual acuity between 6/60-6/18 (46.34%) followed by visual acuity better than 6/18 (39.84%) and then visual acuity worse than 6/60 (13.82%). The higher case of satisfactory visual acuity (better than 6/18) could be a reason for the low prevalence of refractive error in this study.…”
Section: Discussionmentioning
confidence: 99%